Defenses and offences at the trade mark counterfeiting in the Algerian marks law - Rabah, Fadel (revue mofakir; No 12 (2015): مجلـــة المفكــر, 2018)
‫‪Counterfeiting‬‬ ‫‪is‬‬ ‫‪linked‬‬ ‫‪to‬‬ ‫‪the‬‬ ‫‪trade‬‬ ‫‪marks‬‬ ‫‪property‬‬ ‫‪and‬‬ ‫‪its‬‬ ‫‪value‬‬ ‫‪.‬‬ ‫‪the‬‬ ‫‪Algerian‬‬ ‫‪legislator‬‬ ‫‪has‬‬ ‫‪given‬‬ ‫‪abroad‬‬ ‫‪meaning‬‬ ‫‪of‬‬ ‫‪counterfeiting‬‬ ‫‪.‬‬ ‫‪That‬‬ ‫‪is‬‬ ‫‪to‬‬ ‫‪upon‬‬ ‫‪trade‬‬ ‫‪be‬‬ ‫‪can‬‬ ‫‪say,‬‬ ‫‪any‬‬ ‫‪infringement‬‬ ‫‪is‬‬ ‫‪rights‬‬ ‫‪exclusive‬‬ ‫‪marks‬‬ ‫‪considered‬‬ ‫‪as‬‬ ‫‪counterfeiting.‬‬ ‫‪Much‬‬ ‫‪more‬‬ ‫‪counterfeiting‬‬ ‫‪is‬‬ ‫‪a‬‬ ‫;‪fraud‬‬ ‫‪there‬‬ ‫‪are‬‬ ‫‪still‬‬ ‫‪gaps‬‬ ‫‪in‬‬ ‫‪penal‬‬ ‫‪protection‬‬ ‫‪of‬‬ ‫‪trade‬‬ ‫‪marks‬‬ ‫‪law‬‬ ‫‪.‬‬